Asymptotic distinction of counting processes - Lin'kov, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A canonical representation is obtained for the logarithm of the likelihood ratio. Limit theorems describing its asymptotic behavior are proved. Using these theorems, we study the rate of decrease of the probability of an error of the second-kind in the Neyman-Pearson test.